Linear Positionality, Intervality and Semantic Repetition (Distance) of Nominal Morphological Forms - Загнітко, Анатолій П. (Slavic Languages Today: Categories, Structures and Processes, 2021)
Nominal morphological forms of gender, number and case are peculiar when it comes to their status in the categorial system: they include the classification space of membership in the part of speech category and the space of flection; each of these spaces has both internal and external dimensions. The internal dimension involves the classification of all nominal lexemes by gender and their change within the category of number and case, with the assignment to the corresponding type of declension. The external dimension involves the potential of the categorial form, the possibilities of immediate and/or delayed semantic repetition (for nominal morphological forms of gender) and compliance with the regularities of formal (structural) agreement (nominal morphological forms of number and case).This study aims to describe linear positionality involving the manifestation of intervality and semantic repetition (distance) of nominal morphological forms in the modern Ukrainian language, and to trace differential and qualification markers of intervality and discontinuity of these forms. The article analyses intervality and discontinuity models of nominal morphological forms of gender, number and case. The contexts of the use of these forms come from artistic language, the language of modern media as well as from the materials of the Ukrainian National Corpus of the Ukrainian Lingua-Information Fund, National Academy of Sciences of Ukraine. The study applies general scientific methods (observation, induction and deduction, descriptive, elements of statistical methods) and special methodology (historical and linguistic interpretation, functional and component analysis of morphological forms, descriptive method).The use of a special experimental corpus in the study of nominal morphological forms of gender, number and case with a view to identifying the basic and/or additional spectra of semantic repetition, linear/positional fixation and features of discontinuity (semantic and/ or formal) is promising. This line of research will make it possible to distinguish semantic repetition and disontinuity across various discourses. It will also enable us to diagnose the frequency of markers of semantic repetition (distance) of nominal morphological forms of gender, number and case, and to investigate the discontinuity of such forms.